Mindfulness-Based Learning Interventions on Reducing Students' Anxiety Levels - Sri Wiwik Endang Witosari; Neneng Yusmawati Muniroh; Suharyanto Soro; Nana Herdiana Abdul Rahman (Civiliza Publishing, Indonesia., 2026)
Anxiety in adolescents is a serious psychological barrier that affects students' academic performance and emotional well-being in high school, requiring effective and integrated intervention strategies in the educational environment. This study aims to find out the effectiveness of mindfulness-based learning interventions in reducing the level of anxiety of students at SMPN Satu Atap Terpadu Bungursari, Purwakarta. The researcher used a quantitative research paradigm with a quasi-experimental design (Nonequivalent Control Group Design), this study involved 60 students with moderate to high levels of anxiety who were selected through purposive sampling and divided into Experimental Group (n=30) and Control Group (n=30). The experimental group received a structured mindfulness program for 8 weekly sessions, while the control group received no intervention. Data was collected using a valid Adolescent Anxiety Scale through pre-test and post-test procedures, then analyzed using an Independent T Test on Gain Score. The results showed a significant difference (p < 0.001) in the decrease in anxiety scores, where the Experimental Group experienced an average decrease of 22.76 points compared to the Control Group which only experienced a natural decrease of 2.77 points. In conclusion, mindfulness interventions have been proven to be statistically and empirically effective as a method of anxiety mitigation.